Back from basics: integration of science and practice in medical education. Issue 1 (10th October 2017) - Bandiera, Glen; Kuper, Ayelet; Mylopoulos, Maria; Whitehead, Cynthia; Ruetalo, Mariela; Kulasegaram, Kulamakan; Woods, Nicole N.
Abstract : Context: In 1988, the Edinburgh Declaration challenged medical teachers, curriculum designers and leaders to make an organised effort to change medical education for the better. Among a series of recommendations was a call to integrate training in science and clinical practice across a breadth of clinical contexts. The aim was to create physicians who could serve the needs of all people and provide care in a multitude of contexts. In the years since, in the numerous efforts towards integration, new models of curricula have been proposed and implemented with varying levels of success. Scope of Review: In this paper, we examine the evolution of curricular integration since the Edinburgh Declaration, and discuss theoretical advances and practical solutions. In doing so, we draw on recent consensus reports on the state of medical education, emblematic initiatives reported in the literature, and developments in education theory pertinent to the role of integrated curricula. Conclusions: Interest in integration persists despite 30 years of efforts to respond to the Edinburgh Declaration. We argue, however, that a critical shift has taken place with respect to the conception of integration, whereby empirical models support a view of integration as pertaining to both cognitive activity and curricular structure. In addition, we describe a broader definition of 'basic science' relevant to clinical practice that encompasses social and behavioural sciences, as well as knowledge derived from biomedical science. Abstract : The authors propose that integration should be viewed as both a curricular design element and a cognitive process given that what constitutes 'basic' science has evolved to be a much broader concept in modern medical education.